Size matching between fruits and bill gapes differentially affects gulper and masher frugivorous birds - Rojas, Tobias Nicolas; Pizo, Marco A. [UNESP]; Blendinger, Pedro G.; Mangini, G. Giselle; Barberá, Iván (Wiley, 2025)
Birds feeding on fruits (frugivores) affect seed dispersal, seedling establishment and, ultimately, plant assemblage composition. Thus, the mechanisms underlying fruit consumption by birds are central to disentangling the assembly dynamics of mutualistic interactions and their effects on ecosystem functioning. In this regard, the size-matching hypothesis states that the bill gape width is an anatomical filter that allows a bird to ingest a fruit. However, handling behaviour could allow birds to overcome anatomical constraints that limit the consumption of certain fruit species. Here we tested how size matching affects consumption rates and probabilities of frugivores that swallow the fruit unprocessed (gulpers) and those that mandibulate the fruits before ingestion (mashers). Gulpers showed a weak augment in both the rate and probability of fruit consumption as bill-gape width increased relative to fruit diameter. On the other hand, mashers did not respond to size matching either in consumption rate or probability. Altogether our results highlight that other factors besides size are affecting the consumption rate and probability of frugivorous birds. Thus, gulpers and mashers fruit consumption could be subject to different mechanisms regardless size matching. In this regard, fruit traits and animal abilities interact leading to consumption by mashing or gulping the fruit highlighting the dynamic nature of handling behaviour. Altogether, our results warn about the unevaluated overutilization of size-matching as the main mechanism to test the multiple facets of the ecology and evolution of frugivory and seed dispersal. Thus, including handling behaviour and other factors into the mechanisms underlying fruit–frugivore interactions could greatly improve our understanding of mutualistic interactions.
Keywords: ecosystem functioning; frugivores; fruit traits; mutualistic interactions; seed dispersal; trait matching